2021
DOI: 10.1186/s40337-020-00363-8
|View full text |Cite
|
Sign up to set email alerts
|

Engaging primary care providers in managing pediatric eating disorders: a mixed methods study

Abstract: Background The primary care setting offers an attractive opportunity for, not only the identification of pediatric eating disorders, but also the delivery of evidence-based treatment. However, constraints of this setting pose barriers for implementing treatment. For interventions to be successful, they need to take into consideration the perspectives of stakeholders. As such, the purpose of this study was to examine in-depth primary care providers’ perspective of challenges to identifying and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Cachelin & Striegel-Moore, 2006;Cachelin et al, 2001;Cavazos-Rehg et al, 2020;Chowbey et al, 2012;Ciao et al, 2020;Coelho et al, 2021;Couturier et al, 2013;Dayal et al, 2015;Dearden & Mulgrew, 2013;Del Valle et al, 2017;Elran-Barak et al, 2018;Escobar-Koch et al, 2010;Evans et al, 2011;Fitzsimmons-Craft, Balantekin, et al, 2020;Fitzsimmons-Craft, Eichen, et al, 2020;Fitzsimmons-Craft, Krauss, et al, 2020;Forrest et al, 2017;Goodwin & Fitzgibbon, 2002;Gorse et al, 2013;Grammer et al, 2022;Griffiths et al, 2015;Griffiths et al, 2018;Grillot & Keel, 2018;Gulliksen et al, 2015;Hamilton et al, 2022;Hartman-Munick et al, 2021;Hepworth & Paxton, 2007;Herman et al, 2014;Javier & Belgrave, 2019;Kanakam, 2021;Kästner et al, 2021;Lazare et al, 2021;Leavey et al, 2011;Lebow et al, 2021;Linardon, Shatte, et al, 2020;Linardon, Rosato, et al, 2020;Linardon et al, 2021;Lipson et al, 2017;…”
unclassified
“…Cachelin & Striegel-Moore, 2006;Cachelin et al, 2001;Cavazos-Rehg et al, 2020;Chowbey et al, 2012;Ciao et al, 2020;Coelho et al, 2021;Couturier et al, 2013;Dayal et al, 2015;Dearden & Mulgrew, 2013;Del Valle et al, 2017;Elran-Barak et al, 2018;Escobar-Koch et al, 2010;Evans et al, 2011;Fitzsimmons-Craft, Balantekin, et al, 2020;Fitzsimmons-Craft, Eichen, et al, 2020;Fitzsimmons-Craft, Krauss, et al, 2020;Forrest et al, 2017;Goodwin & Fitzgibbon, 2002;Gorse et al, 2013;Grammer et al, 2022;Griffiths et al, 2015;Griffiths et al, 2018;Grillot & Keel, 2018;Gulliksen et al, 2015;Hamilton et al, 2022;Hartman-Munick et al, 2021;Hepworth & Paxton, 2007;Herman et al, 2014;Javier & Belgrave, 2019;Kanakam, 2021;Kästner et al, 2021;Lazare et al, 2021;Leavey et al, 2011;Lebow et al, 2021;Linardon, Shatte, et al, 2020;Linardon, Rosato, et al, 2020;Linardon et al, 2021;Lipson et al, 2017;…”
unclassified
“…We also identified significant improvements in participating PCPs' comfort screening and making referrals for each of AN, BN, BED, ARFID, and OSFED in pediatric patients. Previous studies have demonstrated that physicians have generally low levels of comfort in diagnosing or treating EDs (Anderson et al, 2017; Davidson et al, 2019) but are open to referring patients to other services and working in multidisciplinary teams with ED specialists (Davidson et al, 2019; Lebow et al, 2021). Exposure to the present study's brief video training bolstered PCPs’ comfort in screening and referral for all EDs, which emphasizes that even minimal training can produce change.…”
Section: Discussionmentioning
confidence: 99%
“…Low rates of screening and referral may result in youth with EDs being underdiagnosed into late adolescence and young adulthood (Hornberger & Lane, 2021; Kalindjian et al, 2022). Pediatric primary care providers (PCPs) can play an important role in early detection of symptoms and referral to specialized treatment (Currin et al, 2009; Hornberger & Lane, 2021); however, many PCPs lack training in screening and are unaware of existing referral resources (Banas et al, 2013; Currin et al, 2009; Higgins & Cahn, 2018; Lebow et al, 2021). This gap in training is especially concerning given the rise in youth seeking services for EDs during the COVID‐19 pandemic (Lin et al, 2021; Radhakrishnan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Specialised ED services, when available, are often concentrated in intensive settings in major urban cities, leading to limited treatment spaces and long waitlists. Youth in Canada with mild or early‐stage EDs, and those living outside major cities, often lack access to specialised care (Lebow et al., 2021 ) and any possibility for early detection and intervention. One solution being considered is the spreading of ED services into the community via primary mental health care settings.…”
Section: Early Intervention In Practicementioning
confidence: 99%